2024
DOI: 10.34659/eis.2023.87.4.686
|View full text |Cite
|
Sign up to set email alerts
|

Financial, spatial and systemic determinants of ESG scoring assigned to commercial banks

Marcin Gospodarowicz,
Zbigniew Korzeb,
Paweł Niedziółka
et al.

Abstract: The aim is to verify which financial, spatial and systemic importance variables interact with ESG scoring. Based on data from 628 banks from 63 countries, a multinomial ordered logit model was built with the explanatory variables of Sustainalytics and Moody's ESG scores. Results indicate that membership in the EU, being an SIB, capitalisation, and revenues have a positive effect on ESG. In contrast, an increase in leverage, NPL ratio, and profitability are associated with a deterioration in scorings. Results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Six machine learning approaches were used to forecast ESG rating of companies using firm-specific and macroeconomic predictors in the research (Chowdhury et al, 2023). ESG rating was also analysed by (Gospodarowicz et al, 2024) using financial, spatial and systemic importance variables observed for banks by employing a multinomial ordered logit model. In order to assess the impact of a particular event, the difference-in-differences (DID) model was used in the study (Zhang et al, 2024).…”
Section: Other Methodsmentioning
confidence: 99%
“…Six machine learning approaches were used to forecast ESG rating of companies using firm-specific and macroeconomic predictors in the research (Chowdhury et al, 2023). ESG rating was also analysed by (Gospodarowicz et al, 2024) using financial, spatial and systemic importance variables observed for banks by employing a multinomial ordered logit model. In order to assess the impact of a particular event, the difference-in-differences (DID) model was used in the study (Zhang et al, 2024).…”
Section: Other Methodsmentioning
confidence: 99%